Data from: Herbicide resistance-endowing ACCase gene mutations in hexaploid wild oat (Avena fatua): Insights into resistance evolution in a hexaploid species - Powles, Stephen; Yu, Qin; Ahmad-Hamdani, M. S.; Han, Heping; Christoffers, Michael (Dryad, 2012)
Many herbicide-resistant weed species are polyploids, but far too little
about the evolution of resistance mutations in polyploids is understood.
Hexaploid wild oat (Avena fatua) is a global crop weed and many
populations have evolved herbicide resistance. We studied plastidic
acetyl-coenzyme A carboxylase (ACCase)-inhibiting herbicide resistance in
hexaploid wild oat and revealed that resistant individuals can express
one, two or three different plastidic ACCase gene resistance mutations
(Ile-1781-Leu, Asp-2078-Gly and Cys-2088-Arg). Using ACCase resistance
mutations as molecular markers, combined with genetic, molecular and
biochemical approaches, we found in individual resistant wild-oat plants
that (1) up to three unlinked ACCase gene loci assort independently
following Mendelian laws for disomic inheritance, (2) all three of these
homoeologous ACCase genes were transcribed, with each able to carry its
own mutation and (3) in a hexaploid background, each individual ACCase
resistance mutation confers relatively low-level herbicide resistance, in
contrast to high-level resistance conferred by the same mutations in
unrelated diploid weed species of the Poaceae (grass) family. Low
resistance conferred by individual ACCase resistance mutations is likely
due to a dilution effect by susceptible ACCase expressed by homoeologs in
hexaploid wild oat and/or differential expression of homoeologous ACCase
gene copies. Thus, polyploidy in hexaploid wild oat may slow resistance
evolution. Evidence of coexisting non-target-site resistance mechanisms
among wild-oat populations was also revealed. In all, these results
demonstrate that herbicide resistance and its evolution can be more
complex in hexaploid wild oat than in unrelated diploid grass weeds. Our
data provide a starting point for the daunting task of understanding
resistance evolution in polyploids.
Fig. 5. Plastidic ACCase gene partial sequence alignmentPartial sequence
alignment (from cloned fragments) showing the three haplotype sequences of
the 2088, 1781 and 2078 mutations identified in the present study,
corresponding respectively to the ACCase gene copies Acc1;1, Acc1;2, and
Acc1;3 in wild oat (Christoffers et al., 2002). Note that the sequence
region containing the 1781, 2078 or 2088 codon was not included due to
infrequent informative SNPs. Boxed regions indicate SNPs discriminating
the three haplotypes (GenBank accession AF231335 for Acc1;1-1, AF231334
for Acc1;1-2, AF231336 for Acc1;2 and AF464875 for Acc1;3).Fig. 5 partial
sequence alignment.docFig. S4( d)CAPS analysis of clonesFig. S4 (d)CAPS
marker analysis of ACCase mutations at (a) 1781, (b) 2078 or (c) 2088 in
representative E. coli clones containing the 1122 kb ACCase cDNA insert.
Each lane represents a single clone analysed by each of the three markers.
Note that none of these clones contain more than one mutation (R).
Keywords: Avena fatua; resistance evolution; ACCase gene resistance mutations; Herbicide resistance; Acc1; ACCase mutation